Women Experiences in Interpreting the Islamic Sharia Implementation in Aceh (A Reception Analysis of Women Readers on Serambi Indonesia Daily News) - Putri Maulina (Proceedings of AICS - Social Sciences, 2017)
This research is based on a gender study conducted to the readers of Serambi Indonesia. The study is aimed at looking to the perception of women about Islamic Sharia implementation in Aceh. The analysis was done by using a qualitative approach in Critical Paradigm focusing on the domination and oppression problems, and Reception Analysis method. The theory referred in this study is Reception Analysis Theory to explain the meaning of domination constructed by the media and how the media readers interpreted it and second, Multicultural Feminism is used to explain that every woman does not equally constructed in interpreting oppression of Islamic Sharia implementation in Aceh. The results of the present study in the texts of Serambi Indonesia’s articles showed that in reality, Islamic Sharia implementation which is constructed in the dominant perspective represents the proponent’s viewpoint of Sharia, while the women are portrayed as a “sinner” or “rebel”. On the other hand, there is a variety of interpretations from the readers. There was only one informant from the “dominant-hegemonic position” and three informants were in the “negotiated” position, which tend to have the same or almost the same perception to the message conveyed by Serambi Indonesia. There are other four informants who were in the “opposite” position who are very much against the meaning expressed by Serambi Indonesia, that the texts of Sharia implementation likely tends to disadvantage women.